SUBSTRATE DEGRADATION ABILITY OF CANDIDATES ISOLATE CELLULOLYTIC PROBIOTIC BACTERIA FROM THE LARGE INTESTINE OF BALI PIGS - I G.A.W.K., Putri; Mudita, I M.; Cakra, I G. L. O. (Jurnal Peternakan Tropika; Vol 12 No 1 (2024): Vol. 12 No. 1 Tahun 2024; January - February, 2024)
This study aims to determine the degradation ability of candidate cellulolytic probiotic bacterial isolates from the large intestine of Bali pigs. This research was conducted at the Animal Feed and Nutrition Laboratory, Faculty of Animal Husbandry, Udayana University for 1 month. Substrate degradation ability of cellulolytic probiotic bacteria isolates was carried out using the disc diffusion method, namely by inoculating bacteria on paper discs. Degradability is based on the formation of a clear zone on solid medium containing 1% of the test substrate (avicel, xylan, amylum, protein, and duckweed). The results showed that, on the avicel substrate, bacterial isolate A11 produced the highest score and was statistically significantly different (P<0.05) to isolates A5, B2, C11, and C12. On xylan substrate, bacterial isolates A11 produced higher values and were statistically significant (P<0.05) against isolates A5, B2, C11, and C12. On amylum substrate, bacterial isolates produced a clear zone diameter between 0.50-3.533 cm. On protein and duckweed substrates, the bacterial isolate with code A5 showed higher values quantitatively and was statistically significantly different (P<0.05) to A11, B2, C11, and C12. The results of the substrate degradation ability test showed that the bacterial isolates from the large intestine of Bali pigs with code A5 had the highest degradation abilities on protein and duckweed substrates, isolates coded A11 had the highest degradation abilities on avicel and xylan substrates, and isolate code C11 had the highest degradation abilities on substrates amylum.